Lumbar segment-dependent soft tissue artifacts of skin markers during in vivo weight-bearing forward–Backward bending - Xi, Xin; Ling, Zhi; Wang, Cong; Gu, Chunya; Zhan, Xuqiang; Yu, Haixin; Lu, Siqi; Tsai, Tsung-Yuan; Yu, Yan; Cheng, Liming (Frontiers in Bioengineering and Biotechnology, 2022)
Traditional optical motion capture (OMC) with retro-reflective markers is commonly used to measure joint kinematics, but was also reported with unavoidable soft tissue artefacts (STA) when quantifying the motion of the spine. Additionally, the patterns of the STA on the lumbar spine remain unclear. This study aimed to 1) quantify the in-vivo STA of the human lower back in three-dimensional directions during weight-bearing forward-backward bending and 2) determine the effects of the STA on the calculated flexion angles between the upper and lower lumbar spines, and adjacent vertebrae by comparing the skin marker (SM) and virtual bone marker (VM) based measurements. Six healthy volunteers were imaged using a biplanar radiographic system, and thirteen skin markers were mounted on every volunteer’s lower back while performing weight-bearing forward-backward bending. The STA in the anterior/posterior (AP), medial/lateral (ML), and proximal/distal (PD) directions were investigated. The flexion angles between the upper and lower lumbar segments, and adjacent intervertebral segments (L2–L5) throughout the cycle were calculated. For all the participants, STA continuously increased in the AP direction and exhibited a reciprocal trend in the PD direction. During flexion, the STA at the lower lumbar region (L4–L5:13.5±6.5 mm) was significantly higher than that at the upper lumbar (L1–L3:4.0±1.5 mm) in the PD direction (p<0.01). During extension, the lower lumbar (L4–L5:2.7±0.7 mm) exhibited significantly less STA than that exhibited by the upper lumbar region (L1–L3:6.1±3.3 mm) (p<0.05). The STA at the spinous process was significantly lower than that on both sides in the AP direction (p<0.05). The present results on STA, based on dual fluoroscopic measurements in healthy adult subjects, presented an anatomical direction, marker location, and anatomic segment dependency, which might help describe and quantify STA for the lumbar spine kinematics, and thus help develop location- and direction-specific weighting factors for use in global optimization algorithms aimed at minimizing the effects of STA on the calculation of lumbar joint kinematics in future.